Major Bloodstream Infection-Causing Bacterial Pathogens and Their Antimicrobial Resistance in South Korea, 2017–2019: Phase I Report From Kor-GLASS - Kim, Dokyun; Yoon, Eun-Jeong; Hong, Jun Sung; Choi, Min Hyuk; Kim, Hyun Soo; Kim, Young Ree; Kim, Young Ah; Uh, Young; Shin, Kyeong Seob; Shin, Jeong Hwan; Park, Jeong Su; Park, Kyoung Un; et al. (Frontiers in Microbiology, 2022)
To monitor national antimicrobial resistance (AMR), the Korea Global AMR Surveillance System (Kor-GLASS) was established. This study analyzed bloodstream infection (BSI) cases from Kor-GLASS phase I from January 2017 to December 2019. Nine non-duplicated Kor-GLASS target pathogens, including Staphylococcus aureus, Enterococcus faecalis, Enterococcus faecium, Streptococcus pneumoniae, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter spp., and Salmonella spp., were isolated from blood specimens from eight sentinel hospitals. Antimicrobial susceptibility testing, AMR genotyping, and strain typing were carried out. Among the 20,041 BSI cases, 15,171 cases were caused by one of the target pathogens, and 12,578 blood isolates were collected for the study. Half (1,059/2,134) of S. aureus isolates were resistant to cefoxitin, and 38.1% (333/873) of E. faecium isolates were resistant to vancomycin. Beta-lactamase-non-producing ampicillin-resistant and penicillin-resistant E. faecalis isolates by disk diffusion method were identified, but the isolates were confirmed as ampicillin-susceptible by broth microdilution method. Among E. coli, an increasing number of isolates carried the blaCTX–M–27 gene, and the ertapenem resistance in 1.4% (30/2,110) of K. pneumoniae isolates was mostly (23/30) conferred by K. pneumoniae carbapenemases. A quarter (108/488) of P. aeruginosa isolates were resistant to meropenem, and 30.5% (33/108) of those carried acquired carbapenemase genes. Over 90% (542/599) of A. baumannii isolates were imipenem-resistant, and all except one harbored the blaOXA–23 gene. Kor-GLASS provided comprehensive AMR surveillance data, and the defined molecular mechanisms of resistance helped us to better understand AMR epidemiology. Comparative analysis with other GLASS-enrolled countries is possible owing to the harmonized system provided by GLASS.